2015
DOI: 10.1111/fog.12100
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of demersal fishes in relation to near‐bottom oxygen levels within the California Current large marine ecosystem

Abstract: Various ocean-climate models driven by increased greenhouse gases and higher temperatures predict a decline in oceanic dissolved oxygen (DO) as a result of greater stratification, reduced ventilation below the thermocline, and decreased solubility at higher temperatures. Since spreading of low oxygen waters is underway and predicted to increase, understanding impacts on higher trophic levels is essential. Within the California Current System, shoaling of the oxygen minimum zone (OMZ) is expected to produce com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…As a result, fish time their movements southward to depart waters that are still cooling despite the diminishing ice as summer approaches and to occupy deeper southern waters where temperatures are higher in order to maintain their thermal range. (Youcef et al 2013), it is possible that dissolved oxygen concentration regulates the occurrence of these fish, through sensitivity to changes such as were previously documented for spotted ratfish (Hydrolagus colliei) and petrale sole (Eopsetta jordani; Keller et al 2015). Equally, GLMM showed that, with decreasing bottom oxygen concentrations, fish moved from the northern region southward.…”
Section: Telemetry To Understand the Ecology Of Deep-water Marine Spementioning
confidence: 79%
“…As a result, fish time their movements southward to depart waters that are still cooling despite the diminishing ice as summer approaches and to occupy deeper southern waters where temperatures are higher in order to maintain their thermal range. (Youcef et al 2013), it is possible that dissolved oxygen concentration regulates the occurrence of these fish, through sensitivity to changes such as were previously documented for spotted ratfish (Hydrolagus colliei) and petrale sole (Eopsetta jordani; Keller et al 2015). Equally, GLMM showed that, with decreasing bottom oxygen concentrations, fish moved from the northern region southward.…”
Section: Telemetry To Understand the Ecology Of Deep-water Marine Spementioning
confidence: 79%
“…Climate models driven by global warming conditions predict an overall decline in oceanic dissolved oxygen concentration and a consequent expansion of the oxygen minimum zone (OMZ) as a result of greater stratification, reduced ventilation below the thermocline, and decreased solubility at higher temperatures [53][54][55]. Currently, our limited knowledge of physiological and behavioral responses of individual species hinders modeling efforts on the effects of declining global oxygen or expanding OMZs on ecosystems [10].…”
Section: Discussionmentioning
confidence: 99%
“…Due to deoxygenation of source waters and intensification of upwelling (Garcia-Reyes and Largier, 2010;Sydeman et al, 2014), low-oxygen waters are spreading onto the continental shelf in some regions of the CCLME, bringing them in contact with valuable commercial fisheries (Keller et al, 2015). Moreover, deoxygenation and acidification are linked through biological processes: as organic matter is decomposed, microbial respiration consumes oxygen and produces CO 2 , adding to the burden of CO 2 in seawater that lowers pH and saturation states of carbonate minerals.…”
Section: Oah In the California Current Large Marine Ecosystemmentioning
confidence: 99%
“…Detailed studies of the pteropod Limacina helicina along the US west coast have shown that current levels of anthropogenic CO 2 are already compromising calcification by this important food source for pink salmon, mackerel, and herring (Bednaršek et al, 2014). Diminished fishery catches have been associated with seasonal spatial gradients in dissolved oxygen along the Oregon shelf (Keller et al, 2010(Keller et al, , 2015. Moreover, poor survival of oyster larvae in an Oregon hatchery has been associated with corrosive waters (Barton et al, 2015), and reorganized coastal food webs and increased abundances of pelagic fishes have been associated with historical shifts to lower oxygen conditions in the oceanographically analogous Humboldt Current (Gutiérrez et al, 2009;Salvatteci et al, 2014).…”
Section: Effects On Ecosystemsmentioning
confidence: 99%